Tuberculosis of the Thyroid Gland Presented as a Rapid Enlargement of a Preexisting Goiter - Ibtissem Oueslati; Imen Sakka; Olfa Ismail; Ines Akrout; Adel Marghli; Melika Chihaoui (Case Reports in Endocrinology)
Thyroid involvement with tuberculosis is an uncommon condition even in endemic countries. As its clinical presentation is not specific, diagnosis is often difficult and requires histopathological confirmation. Herein we report an observation of secondary tuberculosis of the thyroid gland in a woman with a type 2 diabetes mellitus and a primary hypothyroidism. She presented with a rapid enlargement of a preexisting goiter without compressive symptoms. The imaging exams showed a voluminous plunging multinodular thyroid gland and multiple bilateral lung nodules. Malignancy was suspected and the patient underwent a total thyroidectomy and a lung biopsy. Histopathological examination revealed multiple tuberculous foci involving both the thyroid gland and the lungs.